Decline in Atlantic wolffish Anarhichas lupus in the North Sea: Impacts of fishing pressure and climate change. Issue 1 (7th December 2021) - Bluemel, Joanna K.; Fischer, Simon H.; Kulka, David W.; Lynam, Christopher P.; Ellis, Jim R.
Abstract: Anarhichas lupus is a boreo‐Arctic species with biological characteristics often associated with vulnerability to overexploitation. Although not commercially targeted in the North Sea, A. lupus is a bycatch species in mixed demersal fisheries. Here we provide an overview of the status of A. lupus in the North Sea, as observed from commercial landings and fishery‐independent trawl survey data. A. lupus was once common across much of the central and northern North Sea but, since the 1980s, have declined in abundance, demographic characteristics (reduced size) and geographical range, with the shallower and more southerly parts of its range most impacted. A. lupus is still relatively frequent in the northern North Sea, where fishing intensity, though decreasing, is high. Bycatch through fishing remains a potential threat and, considering the likely impacts of predicted climate change on cold‐water species, risks of further regional depletion and/or range contraction remain. Whether or not A. lupus is able to re‐establish viable populations in former habitat in UK coastal waters is unknown. Given the lack of data, the precautionary principle would suggest that manageable pressures be minimized where the species and its habitat are at risk of further impacts, and more regular assessments of population status be undertaken.